ANALYSIS OF CAPABILITY, COMMUNICATION QUALITY AND ORGANIZATIONAL LEARNING INFLUENCE ON EMPLOYEE’S PERFORMANCE (Case Study of the Office of Agricultural Service, Salatiga) - Nofi Eko Wahyudi; Mumammad Assegaff (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2011)
Government Instance performance can be run well if employees within the organization havegood capability, and supported by good communication quality and effective organizationallearning. This research has an objective to test a hypothesis about capability, communicationquality, and organizational learning, and their implication on employee’s performance.In this research, the population was 75 respondents by using census technique sampling.Method used was path analysis more to examine predetermined model correlation, rather todiscover the cause. Furthermore to know whether proposed hypothesis was acceptable or not,t-test or significance test was carried out in order to test partial regression coefficient.Research results showed that model and results are acceptable. And later on the researchresults proved positive ones, capability has positive and significant influence on organizationallearning. Communication quality has positive and significant effect on organizational learning.Capability has positive and significant impact on employee’s performance. Communicationquality has positive and significant influence on employee’s performance and organizationallearning has positive and significant influence on employee’s performance. Thus it can be drawna conclusion that organizational learning is not an intervening variable between capability andcommunication quality on employee’s performance.Keywords: Capability, Communication Quality, Organizational Learning, and Employee’s Performance